2017
DOI: 10.1155/2017/5032708
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antidiabetic Medications during the Treatment of Atherosclerosis in T2DM Patients

Abstract: Type 2 diabetes is often associated with arterial atherosclerosis in large blood vessels. We set out to elucidate whether commonly used antidiabetic drugs metformin, sitagliptin, and pioglitazone will reduce atherosclerosis in T2DM patients. We enrolled 176 individuals with type 2 diabetes, which were divided into four treatment groups according to different oral drugs: metformin alone, sitagliptin alone, pioglitazone alone, or combination of metformin and sitagliptin. We assessed changes in glycometabolism, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Through its antiatherogenic effects, by means of a reverse cholesterol transport pathway, elevated levels of HDL are an established method to decrease the risk of cardiovascular injury. The search for new and effective drugs for this purpose continues, and of particular interest are drugs that can increase endogenous levels of HDL, such as pioglitazone, rather than the use of exogenous substances that only mimic the effect of HDL [19]. Kardassis and colleagues showed that glitazones can improve the expression of HDL genes which go in agreement with our findings [28].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Through its antiatherogenic effects, by means of a reverse cholesterol transport pathway, elevated levels of HDL are an established method to decrease the risk of cardiovascular injury. The search for new and effective drugs for this purpose continues, and of particular interest are drugs that can increase endogenous levels of HDL, such as pioglitazone, rather than the use of exogenous substances that only mimic the effect of HDL [19]. Kardassis and colleagues showed that glitazones can improve the expression of HDL genes which go in agreement with our findings [28].…”
Section: Discussionsupporting
confidence: 89%
“…Decreased HDL levels are an established part of every level of atheroma pathophysiology whereby the mechanisms of (1) inhibiting monocyte adhesion to endothelial cells at sites of plaque formation, (2) promoting NO production which suppresses proliferation of the plaque, (3) promoting fibrinolysis, and (4) preventing intra-plaque hemorrhage and many other pleiotropic effects are lost in the setting of decreased HDL levels [19].…”
Section: Discussionmentioning
confidence: 99%
“…DPP4i has been proposed to reduce the overproduction of proinflammatory cytokines and mediators, such as IL-1, IL-6 and tumour necrosis factor-α (TNF-α), C-reactive protein (CRP), possibly mitigating the clinical course of COVID-19. In several human studies, a treatment with sitagliptin significantly decreased plasma concentrations of IL‐6 [ 36 ] and CRP [ 37 ]. In another study, a treatment with vildagliptin was associated with a significant reduction in IL-6 levels [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…IL-6 levels were non-significantly decreased at 3 months among 24 sitagliptin-treated T2DM patients (from 3.5 ± 0.6 to 2.7 ± 0.3 pg/mL, p = ns), 41 whereas they were significantly lowered by sitagliptin in 22 T2DM patients at 12 weeks (by 24%, p < 0.05), 42 as well as at 12 months (from 15.8 ± 6.2 to 12.8 ± 4.3 pg/mL, p = 0.03) in 31 T2DM patients. 53 …”
Section: Introductionmentioning
confidence: 99%